Complications in healthcare integration models and correlated data infrastructure proposition - Ohmar Shiraz Arfeen; Rauf Shahzad Shahrin; Ashraf Zeeshan Ahmad (Jejaring Penelitian dan Pengabdian Masyarakat, 2025)
In healthcare systems, proper data integration models are necessary in order to provide swift treatment for patients. Without integrity and proper management of patient data, it can result in losing many lives due to unwanted delays in getting the necessary data. This study aims to solve this problem by looking at different data-related technological perspectives and discussing which is best suited for the healthcare sector. Multiple papers on different technological perspectives are reviewed to identify the underlying problems and how they can be tackled individually without getting drawbacks in return. Most impactful problems are highlighted and discussed extensively. The findings show that a data warehouse is the most viable option for tackling the highlighted problems due to its highly centralized infrastructure and data consistency. Elaborations are made on the viability of a data warehouse and how it can help healthcare systems in terms of effective data management.